The influence of viscosity on the response of open-cell polymeric foams in uniaxial compression: experiments and theoretical model - Del Piero, Gianpietro; Pampolini, Giampiero (Continuum mechanics and thermodynamics, 2012)
In a preceding paper (Pampolini and Del Piero in J Mech Mater Struct 3:969–981, 2008 ), the response of blocks made of a polymeric open-cell foam subject to uniaxial compression was analyzed. The hysteretic behavior exhibited in cyclic tests was interpreted within the context of nonlinear elasticity, as an effect of strain localization due to the non-convexity of the energy. Here we study some inelastic aspects of the response, such as rate dependence, strength decay after repeated loading, and memory effects. The analysis of some key experiments led us to the conclusion that viscous effects prevail over plasticity and damage. Consequently, we propose here a visco-elastic model, obtained by adding linear visco-elastic elements to our previous chain of nonlinear elastic springs. The paper is completed by the description of a series of experiments and of numerical simulations.